Does the unemployment rate influence influenza immunization rates in Canada? - Reisman, Jane (Université d'Ottawa | University of Ottawa, 2015)
Influenza is a common, and sometimes dangerous, respiratory illness that affects Canada and the rest of the world. The best preventative measure for influenza is an annual influenza vaccination. Understanding what factors affect an individual’s decision to get an influenza immunization is critical for the development and execution of public health policy. Using data from the Canadian Community Health Survey (CCHS) linked with employment data from CANSIM, this study investigates how the unemployment rate, as well as other socioeconomic and health determinants, affects an individual’s decision to get an annual influenza immunization. Temporary worsening of economic conditions (as proxied for by higher unemployment rates) has been shown to lead to better health and better health related behaviors, including for example, more sleep, more exercise and less smoking. In contrast, this study finds that the average change in unemployment rate associated with a recession decreases the likelihood a prime working age individual will get an influenza immunization by 7 percentage points. This might suggest that the opportunity cost of being sick, may outweigh the time cost of getting the immunization for an employed individual. As expected, higher levels of education, income and lower self-perceived health status increase the likelihood that an individual will get an influenza immunization.